Investigating the personality trait towards employee performance at Proton Tanjung Malim Sdn Bhd / Farah Zuhana Ahadun - Ahadun, Farah Zuhana (2019)
Employee performance is the import aspect to be emphasizing, as it is give a huge contribution in achieving organization goals. The purpose of this study was to determine whether agreeableness, conscientiousness, extraversion, emotional stability, and openness to experience are the significant antecedents that influence performance among employees at Proton Tanjung Malim. The populations used in this study were employees working in 8 departments at Proton Tanjung Malim. Sampling technique used was convenience sampling with a total sample of 119 respondents. The data collection used was questionnaires method. Frequency distribution analysis, descriptive test, reliability analysis, Pearson’s correlation analysis and multiple linear regression analysis was used as an analytical technique. The findings revealed that agreeableness and extraversion affect employee performance at Proton Tanjung Malim Sdn Bhd. Therefore, organizations in Malaysia are expected to become a driving force in improving the personality trait of agreeableness, extraversion, emotional stability and openness to experience to improve their current employee performance policy. This can ensure by providing more social interaction activities among employees and sufficient training that can built level confident of employees.